Macrocyclic Ionic Liquids with Amino Acid Residues: Synthesis and Influence of Thiacalix[4]arene Conformation on Thermal Stability - Olga Terenteva; Azamat Bikmukhametov; Alexander Gerasimov; Pavel Padnya; Ivan Stoikov (Molecules, 2022)
Novel thiacalix[4]arene based ammonium ionic liquids (ILs) containing amino acid residues (glycine and L-phenylalanine) in cone, partial cone, and 1,3-alternate conformations were synthesized by alkylation of macrocyclic tertiary amines with N-bromoacetyl-amino acids ethyl ester followed by replacing bromide anions with bis(trifluoromethylsulfonyl)imide ions. The melting temperature of the obtained ILs was found in the range of 50–75 °C. The effect of macrocyclic core conformation on the synthesized ILs’ melting points was shown, i.e., the ILs in partial cone conformation have the lowest melting points. Thermal stability of the obtained macrocyclic ILs was determined via thermogravimetry and differential scanning calorimetry. The onset of decomposition of the synthesized compounds was established at 305–327 °C. The compounds with L-phenylalanine residues are less thermally stable by 3–19 °C than the same glycine-containing derivatives.